Simulated real-world feasibility and feedback session for a lift assistance device, Raymex™: a mixed-method descriptive study - Kalu, Michael; Chaston, Andrew; Alizadehsaravi, Niousha; Veras, Mirella; McArthur, Caitlin (Frontiers in Rehabilitation Sciences, 2024)
BackgroundFall risk and incidence increase with age, creating significant physical and mental burden for the individual and their care provider. Lift assistive devices are used in multiple healthcare facilities, but are generally not portable nor self-operational, limiting their use outside of medical supervision. The Raymex™ lift is a novel lift assistance device within a rollator to address these limitations. We aim to gather user-centered feedback on the Raymex™ lift, set up instructions, safety protocols to improve feasibility and usability, and explore the potential usability as a fall recovery or prevention device.MethodsFour older adults, two informal caregivers and 16 formal caregivers (clinicians and continuing care assistants) participated in a focus group. Participants provided feedback on the Raymex™ lift after viewing a demonstration and using the device. Qualitative and quantitative data were analysized using thematic and descriptive analysis respectively.ResultsParticipants highlighted three major themes: (1) Design features requiring improvement, (2) Positive feedback and suggestions to optimize the Raymex™ lift and (3) Pricing vs. social utility. Participants suggested widening the seat, changing the braking button layout, and lowering the device weight to improve usability. Participants believed the main device feature was fall recovery and had implications for social utility by reducing the need for ambulance visits to the home. Price point led to a concern on affordability for older adults.ConclusionThe feedback gained will advance the development of the Raymex™ lift and may highlight cost-effective design choices for other developers creating related aging assistive technologies.